The influence of teaching supervision on teachers' teaching methods : The Case of a Selected School in Kuala Lumpur - Wu Yue; Mohd Nazri Bin Abdul Rahman (P3I UMSurabaya, 2024)
The case study examines the influence of teaching supervision on teachers' instructional methods at a school in Kuala Lumpur. Using semi-structured interviews and classroom observations, the findings reveal that effective supervision improves teaching strategies, classroom management, and teacher job satisfaction. Supervision helps teachers identify blind spots, incorporate student feedback, and enhance instructional effectiveness and student engagement. However, its success depends on supervisors’ skills, feedback quality, and the school environment. Recommendations include training supervisors, integrating technology, and adopting tailored supervision strategies. These insights provide guidance for strengthening supervision to improve teaching quality and professional development.